(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Thermal actions considered on abutments of integral bridges by the European standard (Eurocode 1) might be in variety of certain situations underestimated. Based on this assumption, thermal monitoring system has been designed and installed into structure of bridge No. 27-117. Temperature profiles in five certain spots are being measured to provide sufficient basis for evaluation of real thermal actions on abutments of integral bridges. For purpose of measurement verification, elementary heat transfer models for finite element method solver were created. These models are being loaded by simplified temperature profiles reached in real time in-situ. Evaluated models provide verification data to compare with measured temperature profiles in structure and might provide information about temperature profiles probably reached during extreme weather situations.